Colorectal cancer: Generalities, diagnosis, and biological therapies as new treatment options - Álvarez Vargas, Michelle (2022)
The development of a malignant adenocarcinoma in the colon's inner layer or rectum wall is known as colorectal cancer. It is attributed to genetic information but also can be acquired due to lifestyle or environmental risk factors. The pathology is usually diagnosed through a colonoscopy. One promising alternative for its treatment is biological therapies. They are designed to improve, focus, or restore immune system function. These can be used to complement traditional treatment (e.g., surgery, radiotherapy, and chemotherapy). Immunotherapy is a classification of biological therapy, and it stimulates the immune system by generating a more effective therapeutic response in cancer treatment. It is possible to identify monoclonal antibodies, vaccines, oncological viruses, and novel methods such as chemoimmunotherapy, in which a cytotoxic agent and an immune response modifier are combined in a single drug. These options have brought promising results through several preclinical and clinical investigations.